Ethics in clinical research - Fakruddin, Md; Chowdhury, Abhijit; Hossain, Md Nur; Mannan, Khanjada Shahnewaj Bin (Bangladesh Journal of Bioethics, 2012)
History of unethical clinical research practice date back to a very long time, though the most remarkable unethical clinical research was those by the Nazis during second world war, which eventually shaken the scientific community and gives birth to the first guideline of ethics in clinical research, the Nuremberg Code. Following Nuremberg code, a number of ethical guidelines has been formulated most important of which are the declaration of Helsinski. To make any research involving human subjects or samples ethically acceptable, a number of key features have to be considered by the scientists. These guidelines are internationally accepted and without following these guidelines, no clinical research is acceptable in the world. Though, there are many countries in the world like Bangladesh, which dont have any ethical guidelines of their own and thus scientists in those countries do not adhere the any ethical guideline while conducting their research. Each country should have their own ethical guidelines and each clinical research institutes should have own ethical review committee to ensure ethical clinical research. DOI: http://dx.doi.org/10.3329/bioethics.v3i3.12560 Bangladesh Journal of Bioethics 2012; 3(3):16-20